2014
DOI: 10.1371/journal.pone.0113223
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Arrays vs. Metaphase-Comparative Genomic Hybridisation and BAC Arrays for Single-Cell Analysis: First Applications to Preimplantation Genetic Diagnosis for Robertsonian Translocation Carriers

Abstract: Comprehensive chromosome analysis techniques such as metaphase-Comparative Genomic Hybridisation (CGH) and array-CGH are available for single-cell analysis. However, while metaphase-CGH and BAC array-CGH have been widely used for Preimplantation Genetic Diagnosis, oligonucleotide array-CGH has not been used in an extensive way. A comparison between oligonucleotide array-CGH and metaphase-CGH has been performed analysing 15 single fibroblasts from aneuploid cell-lines and 18 single blastomeres from human cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…When using mCGH and aCGH to analyze embryos, these chromosomes usually present artifacts regions. [ 14 , 33 ] A positive correlation between DMSO addition and ADO rate reduction in the GEH-MDA method has been demonstrated in this work ( Table 3 ). Moreover, results also showed that the RG-MDA method produces less ADO and better coverage than any experimental condition tested for GEH-MDA.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…When using mCGH and aCGH to analyze embryos, these chromosomes usually present artifacts regions. [ 14 , 33 ] A positive correlation between DMSO addition and ADO rate reduction in the GEH-MDA method has been demonstrated in this work ( Table 3 ). Moreover, results also showed that the RG-MDA method produces less ADO and better coverage than any experimental condition tested for GEH-MDA.…”
Section: Discussionsupporting
confidence: 62%
“…These bands correspond to GC-rich regions and consequently prone to generate artifacts, as has been previously described by mCGH in chromosomes 1p, 16, 17, 19 and 22. [ 14 , 26 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of genomic aberrancy in DTCs in these studies may have been limited by the low resolution of the cCGH method, which makes it less sensitive in detecting small copy number aberrations. 50 However, Holcomb and colleagues 49 used high-resolution array-based CGH analysis in small pools of EPCAM-positive DTCs; they reported that cells isolated from patients with localized prostate cancer had significantly fewer aberrations vs. their corresponding primary tumors. 49 …”
Section: Discussionmentioning
confidence: 99%